White collar 1‐induced photolyase expression contributes to UV‐tolerance of Ustilago maydis. Issue 2 (20th December 2015) - Brych, Annika; Mascarenhas, Judita; Jaeger, Elaine; Charkiewicz, Elzbieta; Pokorny, Richard; Bölker, Michael; Doehlemann, Gunther; Batschauer, Alfred
Abstract: Ustilago maydis is a phytopathogenic fungus causing corn smut disease. It also is known for its extreme tolerance to UV‐ and ionizing radiation. It has not been elucidated whether light‐sensing proteins, and in particular photolyases play a role in its UV‐tolerance. Based on homology analysis, U. maydis has 10 genes encoding putative light‐responsive proteins. Four amongst these belong to the cryptochrome/photolyase family (CPF) and one represents a white collar 1 ortholog ( wco1 ). Deletion mutants in the predicted cyclobutane pyrimidine dimer CPD‐ and (6–4)‐photolyase were impaired in photoreactivation. In line with this, in vitro studies with recombinant CPF proteins demonstrated binding of the catalytic FAD cofactor, its photoreduction to fully reduced FADH − and repair activity for cyclobutane pyrimidine dimers (CPDs) or (6–4)‐photoproducts, respectively. We also investigated the role of Wco1. Strikingly, transcriptional profiling showed 61 genes differentially expressed upon blue light exposure of wild‐type, but only eight genes in the Δwco1 mutant. These results demonstrate that Wco1 is a functional blue light photoreceptor in U. maydis regulating expression of several genes including both photolyases. Finally, we show that the Δwco1 mutant is less tolerant against UV‐B due to its incapability to induce photolyase expression. Abstract : We show in this contribution that the phytopathogenic fungus Ustilago maydis responds to blue light under control of white collar 1 (Wco1). Among the blue light‐induced genes are the photolyase DNA repair enzymes. The Δ wco1 mutant is less tolerant against UV‐B consistent with lack of photolyase induction in the mutant.